2018
DOI: 10.3389/fpsyg.2018.02605
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mediating Role of Self-Efficacy and Self-Esteem on the Effect of Workload on Burnout’s Influence on Nurses’ Plans to Work Longer

Abstract: At the present time, we know that there is a positive relationship between self-efficacy and self-esteem in which positive beliefs about one’s own efficacy increase one’s sense of self-worth as stressful situations of a heavy workload are coped with successfully, and this, in turn, affects the nurses’ plans to work longer. Analyze the mediating role of self-efficacy and self-esteem in the effect of workload, measured as the number of users attended to during a workday, on burnout in nursing professionals. A sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 45 publications
9
55
1
1
Order By: Relevance
“…Employees' beliefs as to the extent of their control over their work setting can mitigate the negative impact of work demands and have a positive impact on engagement and job performance (Bakker and Demeoruti, 2017;Molero et al, 2018). Employees' beliefs may also be a useful factor for understanding people's ability to accept help from others.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Employees' beliefs as to the extent of their control over their work setting can mitigate the negative impact of work demands and have a positive impact on engagement and job performance (Bakker and Demeoruti, 2017;Molero et al, 2018). Employees' beliefs may also be a useful factor for understanding people's ability to accept help from others.…”
Section: Efficacymentioning
confidence: 99%
“…Selfefficacy influences how people behave and how one thinks and feels about the future (Bandura, 1977(Bandura, , 1997. Hence, employees' self-efficacy beliefs are key to the ways in which they perceive their work context, especially when they face demanding and potentially stressful job demands (Ventura et al, 2015;Molero et al, 2018). Jaeckel et al (2012) distinguished between two forms of self-efficacy.…”
Section: Efficacymentioning
confidence: 99%
“…Therefore, mindfulness practice by workers in this sector facilitates awareness and being in the present moment, enabling recognition of the empathetic experience and promoting critical examination [58]. Improvement in the work climate and nursing action derive from both progress in working conditions and developing individual internal resources, maybe which, in turn, foster coping with highly stressful conditions, exhaustion and emotional impact [16,[59][60][61]. As mindfulness is a potentially modifiable individual characteristic, its intervention can generate positive results in the scope of healthcare [62].…”
Section: Empathy In Healthcare Professionals and Their Relationship Wmentioning
confidence: 99%
“…Brown () stated that positive beliefs of self‐efficacy are a key modifiable cognition, which could protect an individual from the effects of WS. When individuals have positive beliefs of personal self‐efficacy, they tend to be more adaptable to handling workplace stressors (Bandura, ), experience less workplace burnout (Molero, Perez‐Fentes, & Gazquez, ; Yao et al, ), have fewer mental health problems (Laschinger et al, ) and are more engaged in their jobs (Perez‐Fuentes et al, ). The empirical studies revealed that stressors relating to work and workloads significantly influenced nurses' self‐efficacy (Molero et al, ).…”
Section: Introductionmentioning
confidence: 99%